The gentleman's mistress : Illegitimate relationships and children, 1450--1640 - Thornton, Tim; Carlton, Katharine (Manchester University Press, 2019)
This book explores continuities in the extra-marital relationships of the gentry and nobility in the north of England. A major contribution to debates on sex and marriage, family, kinship and gender, it challenges assumptions about the impact of Protestantism and other changes to elite culture.